Proteomic Insight into the Response of Arabidopsis Chloroplasts to Darkness - Wang, Jing (PLoS One, 2016)
Chloroplast function in photosynthesis is essential for plant growth and development. It is well-known that chloroplasts respond to various light conditions. However, it remains poorly understood about how chloroplasts respond to darkness. In this study, we found 81 darkness-responsive proteins in Arabidopsis chloroplasts under 8 h darkness treatment. Most of the proteins are nucleus-encoded, indicating that chloroplast darkness response is closely regulated by the nucleus. Among them, 17 ribosome proteins were obviously reduced after darkness treatment. The protein expressional patterns and physiological changes revealed the mechanisms in chloroplasts in response to darkness, e.g., (1) inhibition of photosystem II resulted in preferential cyclic electron flow around PSI; (2) promotion of starch degradation; (3) inhibition of chloroplastic translation; and (4) regulation by redox and jasmonate signaling. The results have improved our understanding of molecular regulatory mechanisms in chloroplasts under darkness.